ASOSIASI HLA-DRB1* DAN HLA-DQB1* DENGAN IGM-RF SERUM PADA ARTRITIS REUMATOID - Joewono Soeroso; Ferdinandus Maria Judajana; Handono Kalim (Indonesian Association of Clinical Pathologist and Medical laboratory, 2012)
Rheumatoid arthritis (RA) is a chronic progressive polygenic autoimmune disease with a high socio-economic burden. Genetic polymorphisms expressed as a shared epitope (SE) at hypervariable regions of HLA-DRB1*01/*04/*10/*14 and linkage disequilibriums of HLA-DRB1*-HLA-DQB1* with some microorganisms, increase the risk of RA. Shared epitopes are also related with the increase of serum IgM-RF as well. A cross-sectional study on 48 RA patients diagnosed by ACR Criteria 1987 from 6 hospitals in Java and Bali was done to determine the associations of HLA-DRB1* and HLA-DQB1* alleles with serum IgM-RF levels. The presence of HLA-DRB1* and HLA-DQB1* alleles were assessed through PCR-SSO. Serum IgM-RF levels (IU/mL) were assessed through ELISA. Man-Whitney U tests were used to measure the associations. Value of p<0.05 is considered to be statistically significant. The results showed that mean ranks IgM-RF levels of subjects who are bearing HLA-DRB1*04 compared to subjects who are not bearing HLA-DRB1*04 were 34.10 IU/ml (n=10) vs 21.97 IU/ml (n=38), p=0.014. While, the mean ranks of IgM-RF levels of subjects who are bearing haplotype combination of HLA-DRB1*04-HLA-DQB1*03 vs subjects who are not bearing haplotype combination of HLA-DRB1*04- HLA-DQB1*03 were 32.89 IU/mL (n=9) vs 22.56 IU/mL (n=39) (p=0.046). It is concluded that there are association of HLA-DRB1*04, and haplotype combination of HLA-DRB1*04-HLA-DQB1*03 with increased levels of IgM-RF among Indonesians with RA.